The Effects of Perceived Coach Leadership on Athlete’s Burnout: Implications for Quality of Coach-Athlete Relationship - Chrissel Jay Duhaylungsod; Kate Icalina; Jet Clayton Longakit (Journal of Coaching and Sports Science)
Background: Numerous studies have explored the effect of coach-athlete relationships on athletes' burnout, yet there has been a notable gap in the mediating role of coach leadership.